Savings Mobilization and Financial Development during the Multicurrency Regime Period in Zimbabwe - Tsaurai, Kunofiwa (Journal of Economics and Behavioral Studies, 2017)
This paper seeks to investigate the relationship between savings and financial development in Zimbabwe using both autoregressive distributive lag (ARDL) and vector error correction model (VECM) approaches for comparison purposes with monthly time series data from January 2009 to August 2015. Four distinct hypotheses emerged from the literature and these are the savings-led financial development, financial development-led savings, feedback effect and the insignificant/no relationship hypothesis. The existence of diverging and contradicting views in empirical literature on the subject matter is evidence that the linkage between savings and financial development is still far from being concluded. Both F-Bounds and Johansen co-integration tests observed that there is a long run relationship between savings and financial development in Zimbabwe. What is even more unique about this study is that both ARDL and VECM noted the presence of a bi-directional causality relationship between savings and financial development in the short and long run in Zimbabwe. The implication of this study is that in order to increase economic growth, Zimbabwe authorities should increase savings mobilization efforts in order to boost financial development, which in turn attracts more savings inflow into the formal financial system.